Easy to implement ventilated sunspace for energy retrofit of condominium buildings with balconies. (October 2019) - Allesina, Giulio; Ferrari, Chiara; Muscio, Alberto; Pedrazzi, Simone
Abstract: Energy retrofit of the facade of condominium buildings may be a difficult task because thermal bridges such as those due to balconies, common elements in the architecture of many countries, are often arduous to correct by added insulation due to several constraints. An alternative retrofit approach is therefore analyzed, easy to implement and relatively inexpensive. It consists in changing a balcony into a ventilated sunspace during the cold season, exploiting solar gains to compensate heat loss. More specifically, transparent plastic roll-up sheets are installed along the balcony perimeter, removable in the hot season, to enclose the volume between two superposed balcony slabs. The obtained sunspace is then used as a pre-heating chamber for a single-flow ventilation system that ensures the air changes required indoors. Heat gain to the indoor environment can thus be increased with respect to a simpler sunspace without ventilation, and possibly modulated along the day by proper control of the flow rate. In this work, the proposed approach and a small-scale physical model are presented. The model will serve to validate analyses aimed to forecast and optimize the performance of ventilated sunspaces built around balconies. Highlights: The envelope of condominium buildings with balconies is arduous to retrofit. A balcony can be converted into a sunspace enclosed by plastic roll-up sheets. It can then be exploited as preheating chamber of a single-flow ventilation system. Solar gains are thus increased with relatively low cost and ease of implementation. A small scale model has been built to test the retrofit approach.